PENENTUAN KARAKTERISTIK PRODUK SEBAGAI BAHAN PERTIMBANGAN DALAM PERENCANAAN PENGEMBANGAN PRODUK KERIPIK TEMPE. ( STUDI KASUS DI INDUSTRI KERIPIK TEMPE ”ABADI” MALANG ) - Dian Wijaya; Sri Maryani Santoso; Nur Hidayat (Department of Agro-industrial Technology, University of Brawijaya, 2012)
The objectives of this research are to determine the product characteristics that will meet to satisfy of costumer and know customer satisfaction level due to change in redesign of tempe crackers. The method that in used are Kano method. The Kano model of costumer satisfaction classifies product characteristic based on costumer perceiving and their influencing on costumer satisfaction.The results in this research showed that four characteristics of product would have highly significant influencing on the satisfaction and unsatisfaction of the costumers, there are presentation of product figure at packaging material, at a level of IBT 0.87 and IWT -0.93, texture of product sowed with celery leaves at a level of IBT 0.85 and IWT -0.90, tempe crackers with curry sense at a level of IBT 0.85 and IWT -0.81, and tempe crackers with round shape at a level of IBT 0.63 and IWT -0.72 Keywords: model Kano, Sample, Product Characteristics